(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The study of emancipation and increased status enjoyed by women in a society are goodindicators of that society’s progress. Despite the fact that countries’ legal and cultural landscapes havealways been impacted by gender, women have always remained a minority group in terms of global powerand influence, despite their numerical equality. As long as half of the people is left behind, no country canprogress in any way — socially and economically, as well as politically. Any civilization that denies womenthe fundamental rights of equality and freedom is committing a grave offence against human dignity,human rights, and development. During the Vedic period in India, female brilliance was at its peakhowever, it has since experienced a steady fall. As soon as we gained our independence, our country’sConstitution was amended to include protections for women and children as well as the wonderfulconcepts of equality, liberty, and social justice. Many laws were created to defend women’s rights andpromote their dignity in accordance with the Constitution’s mandate. The right to equal pay for equalwork, maternity benefits, Inheritance ownership or inheritance, and protection against husband crueltythrough divorce or judicial separation are a few examples of such legal innovations. As a result of theselegislative changes, a false impression has been created about Indian women’s place in Indian society.Even while laws have been passed to aid some women, in practise only a small minority have reaped thebenefits of those reforms. As a result of the fact that the majority of Indian women are still uneducatedand unaware of their legal rights, very few of them own any real estate. As a result, women in India stayat the bottom rungs of society, both economically and socially.